Modeling the Causal Linkages Between Trade Openness, Innovation, Financial Development and Economic Growth in Asian Countries - Wang, Nanyue; Seyedmatin, Pourya (Asian Journal of Empirical Research, 2020)
The relationship among innovation, economic growth, trade openness and financial development has been an interesting topic in context of research, and many researchers have done significant work on these relationships. As far as economic growth is concerned, the impact of financial development, trade openness and innovation has been considered to be the most essential. In the similar context, the current study has been designed with the motive to find out and investigate the casual relationships between innovation, financial development, trade openness and economic growth of Asian countries. Based on the context of Asian countries, the data has collected of Asian countries including Bangladesh, Indonesia, Japan, Philippines, Thailand and Turkey, for the time period of 1980 to 2018. The Cobb Douglas production model has been used to get assistance for the achievement of the objectives of the current study. The collected data was analyzed by applying unit root test and panel VAR estimation model in the study. The results have indicated that there is no casual relationship among financial development and innovation. In the same way, no casualty has been found among trade openness and innovation. Contrarily, unidirectional casual relations have been found between economic growth along with financial development and in the same way, between trade openness and financial development. Lastly, this study has found a “bidirectional” casual relationship amid economic growth and trade openness. This study provides different implications especially for the policy makers of the Asian countries who can get assistance from this study to enhance their economic growth.